1974
DOI: 10.1071/bi9740293
|View full text |Cite
|
Sign up to set email alerts
|

Primordial Follicle Numbers in Ovaries and Levels of LH and FSH in Pituitaries and Plasma of Lambs Selected for and against Multiple Births

Abstract: The numbers of primordial follicles in ovaries of ewe lambs, from two groups of Peppin Merinos that had been selected for (T group) and against (0 group) mUltiple births, were estimated at birth, 7 days and 5 months of age. Peripheral plasma and anterior pituitary levels of LH and FSH were determined by radioimmunoassay in the lambs at 5 months of age. These lambs were either entire or unilaterally ovariectomized (hemispayed) at 7 days of age.There was no difference in primordial follicle numbers between lambs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Although primordial follicle formation and the initiation of follicle development occurs in the ovary of many mammals during fetal development [33][34][35] (except for the rodent where these occur in the immediate postpartum period) [17], subsequent folliculogenesis extends throughout the reproductive life of the female. Considerable progress has been made in our understanding of the regulation of physiological and molecular events involved in follicle maturation and ovulation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Although primordial follicle formation and the initiation of follicle development occurs in the ovary of many mammals during fetal development [33][34][35] (except for the rodent where these occur in the immediate postpartum period) [17], subsequent folliculogenesis extends throughout the reproductive life of the female. Considerable progress has been made in our understanding of the regulation of physiological and molecular events involved in follicle maturation and ovulation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In order to make realistic comparisons between genotypes, adjustment must therefore be made for differences in the distribution of birth types. In the earlier study of Trounson et al (1974), in which data were not corrected for litter size at birth, the numbers of primordial follicles were significantly different in lambs from T and 0 flocks. Mter adjustment for litter size ,and sire in the present experiment the T and 0 were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Tassell et al Follicles were classified as described by Trounson et al (1974) and Tassell et al (1978). Primordial, small and large growing (non-vesicular), and partially and fully formed vesicular follicles were counted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first studies on the relationship between the populations of primordial follicles and ovulation rate examined the relation between the number of germinal cells present in the ovary at birth in females from a given genetic line and the mean ovulation rate of that line (sheep: Land, 1970;Trounson, Chamley, Kennedy & Tassell, 1974;Cahill, Mariana & Mauléon, 1979;mouse: Iones & Krohn, 1961 ; rat: Land, de Reviers, Thompson & Mauléon, 1974). These authors all showed that there is a negative correlation between the number of primordial follicles and ovulation rate.…”
Section: Introductionmentioning
confidence: 99%